2002
DOI: 10.1007/s007010200032
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Slowly varying pressure oscillations in the cranial enclosure are well known, especially intracranial pressure waves as best described by the pioneering works of Janny and Lundberg. Nevertheless, in spite of over twenty five years research on intracranial pressure waves, their origin and regulation remain unclear but are often considered only as pathological. Our aim was to review data on these phenomena to clarify their biological status and the role that they could play in the management of patients sufferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Recently, ICP variability has also been examined with mathematical tools using e.g. frequency domain approaches, confining the ICP analysis to variations within specified slow-wave ICP frequencies [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, ICP variability has also been examined with mathematical tools using e.g. frequency domain approaches, confining the ICP analysis to variations within specified slow-wave ICP frequencies [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICP variations have generated interest since the development of ICP monitoring in the NIC [17]. Various ICP wave forms have been examined such as Lundberg's type A wave (plateau wave) with amplitudes above 50 mmHg, a duration above 5 min and occurring at a relatively low frequency [18]. Type B waves have a higher frequency at approximately 1-2 waves/min and with a lower amplitude around 5 mmHg.…”
Section: Icpv: Explanatory Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that a change in slow waves of the ICP signal in TBI indicates an autoregulatory response to changes in cerebral perfusion [16]. B-waves have also been shown to occur simultaneously with vascular oscillations in an experimental study with incremental ICP increases [17].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of Lundberg A waves, which are sustained sharp increases in mean ICP lasting 5–20 min, may also signify diminishing compliance ( Figure 5 C) [ 55 ]. Lundberg B waves, which are clustered cyclic elevations in ICP occurring at a rate of 0.33–3 cycles per minutes with overall cluster duration of 5–30 min [ 56 , 57 ], are non-specific indicators of diminished compliance as they can also be present in patients with normal ICP [ 55 ].…”
Section: Approaches To Improving Utility Of Invasive Icp Monitorinmentioning
confidence: 99%